The Impact of Electronic Word of Mouth (E-WoM) on Brand Equity of Imported Shoes: Does a Good Online Brand Equity Result in High Customers’ Involvements in Purchasing Decisions? - Syahrivar, Jhanghiz; Ichlas, Andy Muhammad (The Asian Journal of Technology Management (AJTM), 2018)
Abstract. In the fourth industrial revolution, technology plays a greater role in influencing customers’ preferences towards certain brands. Internet and social media platform has become a powerful marketing tool for sharing relatable experiences among customers online. The objective of this research was to investigate the role of Electronic Word of Mouth (EWOM) on Brand Equity and its impact on Purchasing Decision of Imported Shoes in Bekasi, Indonesia. This research used primary data by distributing questionnaires to 162 customers of imported shoes. The data of this research was analyzed through SPSS and the hypotheses were tested by employing Binomial Logistic Regression. The result of this research suggested that E-WOM has a positive impact on all dimensions of Brand Equity and a good online Brand Equity generates high customers’ involvements in purchasing decisions. The highest influencer towards Purchasing Decision was Brand Awareness; whereas the least influencing variable was Perceived Quality. Keywords:  Electronic word of mouth (EWOM), brand association, brand awareness, brand loyalty, perceived quality, purchasing decision, technology in marketing